Review: Faith in Hebrews. Analysis within the Context of Christology, Eschatology, and Ethics - Browne, Arnold S. (The journal of theological studies, 2002)
Faith in Hebrews. Analysis within the Context of Christology, Eschatology, and Ethics Victor (Sung‐Yul) Rhee xvi + 280 New York (Studies in Biblical Literature, 19.) Peter Lang 2001 £38 0 8204 4531 2